Determinants of self-rated health of Francophone seniors in a minority situation in Canada - Alimezelli, Hubert Tote; Leis, Anne; Karunanayake, Chandima; Denis, Wilfrid (Linguistic Minorites and Society / Minorités linguistiques et société, 2013)
Résumé La tendance actuelle montre que les institutions des services de santé et les gouvernements répondent de façon inadéquate aux besoins de plus en plus nombreux d’accès aux services de santé par les populations vieillissantes du Canada et d’autres pays développés. Après l’analyse de l’enquête post-censitaire 2006 de Statistiques Canada sur la Vitalité des Minorités de Langue Officielle, cette étude démontre qu’outre l’age, et en plus d’autres déterminants, les barrières linguistiques auxquelles font face les aînés de langue officielle en situation minoritaire affectent davantage l’autoévaluation de leur santé. Cette étude suggère quelques pistes de solution dont la compréhension des réalités contextuelles, l’amélioration de l’environnement linguistique et des services de santé dans la langue minoritaire. Mots-clés : déterminants de la santé, statut minoritaire, santé perçue, minorités linguistiques, aînés Abstract Current trends show that governments and health institutions in Canada and other developed nations are responding inadequately to the growing need for health services of the increasingly aging population. The Analysis of Statistics Canada’s 2006 post-census Survey on the Vitality of Official Language Minorities show that in addition to age and other socio-demographic determinants, linguistic barriers affect the self-rated health of seniors of official languages living in a minority situation. This study suggests among other things a greater understanding of Official language minorities’ contextual realities, the improvement of both the linguistic environment and services in the minority language. Keywords: health determinants, minority status, self-rated health, linguistic minorities, older adults

Améliorer la santé et le bien-être des Madelinots anglophones. Une évaluation des besoins : mieux comprendre la situation actuelle des aînés - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Anglophone Magdalen Islanders, 2017)

Multilingualism (but not always bilingualism) delays the onset of Alzheimer disease: Evidence from a bilingual community - Chertkow, Howard; Whitehead, Victor; Phillips, Natalie; Wolfson, Christina; Atherton, Julie; Bergman, Howard (Alzheimer Disease and Associated Disorders, 2010)
A recent paper by Bialystok et al in Neuropsychologia (vol. 45, pgs. 459 to 464) suggested that early bilingualism produced a statistically significant 4.1-year delay in onset of memory loss symptoms in older individuals with Alzheimer disease, possibly reflecting an increase in the cognitive reserve of these individuals. That study focused on multilingual elderly patients of whom 90% were immigrants. Our memory clinic, in Montreal Canada, has the advantage of having a large set of individuals who are either multilingual immigrants to Canada, or who are nonimmigrants but raised in both official languages of Canada—French and English. We thus attempted to replicate the above findings using a larger cohort in a different setting. We examined age at diagnosis of Alzheimer disease and age at symptom onset for all unilingual versus multilingual participants, and then for those who were nonimmigrant English/French bilinguals. Overall, we found a small but significant protective effect of more than 2 languages spoken, but we found no significant benefit in bilinguals overall in relation to age at diagnosis or age at symptom onset. However, in the immigrant group, the results mirrored those of Bialystok et al with 2 or more languages delaying the diagnosis of Alzheimer disease by almost 5 years. A trend toward the same effect was also seen in nonimmigrants whose first language was French. In contrast, in nonimmigrants whose first language was English, no such effect was found. These results are discussed in relation to the earlier findings and the theory of cognitive reserve.

Bien vieillir dans sa langue, sa culture et sa communauté. Soutien d’institutions fédérales clés et portrait des aînés anglophones du Québec - Commissariat aux langues officielles (Gouvernement du Canada, 2013)

Profil statistique 2016 des personnes âgées francophones au Canada : faits saillants [infographie] - Fédération des aînées et aînés francophones du Canada (2019)

Profil statistique 2016 des personnes âgées francophones au Canada [Rapport] - Fédération des aînées et aînés francophones du Canada (2019)

Promoting the health and well-being of English-speaking seniors in Quebec. A community model - Kueber, Rusell (Community Health and Social Services Network / Réseau communautaire de santé et de services sociaux, 2019)

Promotion de la santé et du bien-être des aînés d’expression anglaise du Québec : un modèle communautaire - Kueber, Russell (Réseau communautaire de santé et de services sociaux / Community Health and Social Services Network, 2019)

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.

Enjoying your senior years in your own language, culture and community. Federal support from key institutions and a portrait of English-speaking seniors in Quebec - Office of the commissioner of official languages (Federal support from key institutions and a portrait of English-speaking seniors in Quebec, 2013)

Socio-demographic profile of the population aged 65 and over. Province of Québec. Based on the 2016 census of Canada - Pocock, Joanne (Community Health and Social Services Network, 2018)

Culture, language and self- assesments of future health: Anglophones and Francophones in Quebec’s Eastern Townships - Stout, Dale; Charpentier, Claude; Chiasson, Myriam; Filion, Emmalie (Journal of Eastern Townships Studies, 2009)
This study examines subjective ratings of health (SRH) by Francophones and Anglophones living in the Eastern Townships. Global self-ratings of health are regarded as sensitive predictors of future health states, mortality, functional decline and disability, and utilization of the health-care system. Yet despite their pragmatic value, SRH are poorly understood. Along with a spontaneous monitoring of present health states, culture and language are listed as determinants of SRH. Few studies exist, however, that clearly delineate the direction and degree of effect that culture and language have on SRH. Adopting a temporal assessment of SRH, we asked 358 Anglophones (N=176) and Francophones (N=171) from the Eastern Townships, aged 18 to 95, to rate their health in the past, present, and future. To isolate culture and language effects we also asked participants to rate their future health if they “remained in Quebec”. Results revealed a significant interaction between age and temporal ratings of health (SRH). Turning to the effects of location (unspecified or “in Quebec”) on future health ratings, there was a significant interaction with language. Post hoc tests revealed no significant differences in Francophones’ future health ratings (unspecified or “in Quebec”) but a significant ratings drop was noted for Anglophones if they “remained in Quebec”. After controlling for bilingualism, this interaction remained statistically significant.

The effects of age and culture on subjective well-being: A case study in the Eastern Townships - Stout, Dale; Filion, Emmalie; Chiasson, Myriam; de Man, Anton; Charpentier, Claude; Pope, Megan (Journal of Eastern Townships Studies, 2008)
The present study of diachronous ratings of subjective well-being (SWB) was modeled on research undertaken by Staudinger, Bluck & Herzberg (2003). In addition, we were interested in determining the effects of culture and context (where one lives) on SWB ratings. To gage these effects, we included the factor of mother tongue and altered the Life Satisfaction Questionnaire by adding a question concerning expected well-being in Quebec. We asked 350 Anglophones and Francophones from the Eastern Townships, aged 18 to 95, to rate their SWB in the past, present, future, and future ‘in Quebec’. The results concerning the effects of chronological age on diachronistic SWB ratings followed the patterns of previous research: young people (aged 18–38) rate past SWB lower than present SWB and future SWB much higher; middle-aged people (aged 39–64) rate their SWB the same regardless of time; And the elderly (67–95) rated past SWB higher than the present and their future SWB much lower. There were no differences between Anglophones or Francophones. Further analysis revealed the disturbing finding that the oldest participants rated their current SWB significantly lower than the other two age groups. In the second half of our study we found that by simply asking Francophones and Anglophones to rate their SWB in the future – first unspecified as to location, and then in a future ‘if they stay in Quebec’ – produced different response patterns. Both future SWB ratings were the same for Francophones, indicating that the questions were simply redundant. The Anglophones, on the other hand, rated their future SWB in Quebec consistently lower than an unspecified future.

Access to health care services: East-End Montreal (Quebec) English-speaking elderly experience [master's thesis, McGill University] - Thomas, Rosemary Hellen. (2008)

Social networks and self-rated health in two French-speaking Canadian community dwelling populations over 65 - Zunzunegui, Maria Victoria; Koné, A.; Johri, Mira; Béland, François; Wolfson, Christina; Bergman, Howard (Social Science & Medicine, 2004)
The objective was to evaluate the associations between older persons’ health status and their social integration and social networks (family, children, friends and community), in two French-speaking, Canadian community dwelling populations aged 65 years and over, using the conceptual framework proposed by Berkman and Thomas. Data were taken from two 1995 surveys conducted in the city of Moncton (n=1518) and the Montreal neighbourhood of Hochelaga-Maisonneuve (n=1500). Social engagement (a cumulative index of social activities), networks consisting of friends, family and children and social support were measured using validated scales. Multiple logistic regressions based on structured inclusion of potentially mediating variables were fitted to estimate the associations between health status and social networks. Self-rated health was better for those with a high level of social integration and a strong network of friends in both locations. In addition, in Hochelaga-Maisonneuve family and children networks were positively associated with good health, though the effect of friend networks was attenuated in the presence of disability, good social support from children was associated with good health. Age, sex and education were included as antecedent variables; smoking, alcohol consumption, exercise, locus of control and depressive symptoms were considered intermediary variables between social networks and health. In conclusion, social networks, integration and support demonstrated unique positive associations with health. The nature of these associations may vary between populations and cultures.